The admissions process of a bachelor of science in nursing program: initial reliability and validity of the personal interview. - Carpio B; Brown B (Canadian Journal of Nursing Research)
The undergraduate nursing degree program (B.Sc.N.) at McMaster University School of Nursing uses small groups, and is learner-centered and problem-based. A study was conducted during the 1991 admissions cycle to determine the initial reliability and validity of the semi-structured personal interview which constitutes the final component of candidate selection for this program. During the interview, three-member teams assess applicant suitability to the program based on six dimensions: applicant motivation, awareness of the program, problem-solving abilities, ability to relate to others, self-appraisal skills, and career goals. Each interviewer assigns the applicant a global rating using a seven-point scale. For the purposes of this study four interviewer teams were randomly selected from the pool of 31 teams to interview four simulated (pre-programmed) applicants. Using two-factor repeated-measures ANOVA to analyze interview ratings, inter-rater and inter-team intraclass correlation coefficients (ICC) were calculated. Inter-team reliability ranged from .64 to .97 for the individual dimensions, and .66 to .89 on global ratings. Inter-rater ICC for the six dimensions ranged from .81 to .99, and .96 to .99 for the global ratings. The item-to-total correlation coefficients between individual dimensions and global ratings ranged from .8 to 1.0. Pearson correlations between items ranged from .77 to 1.0. The ICC were then calculated for the interview scores of 108 actual applicants to the program. Inter-rater reliability based on global ratings was .79 for the single (1 rater) observation, and .91 for the multiple (3 rater) observation. These findings support the continued use of the interview as a reliable instrument with face validity. Studies of predictive validity will be undertaken.